2017
DOI: 10.1246/cl.170654
|View full text |Cite
|
Sign up to set email alerts
|

3-Aminopropanethiol versus 2-Aminoethanethiol Leading to Different S-bridged Multinuclear Structures Composed of Rhodium(III) Octahedrons

Abstract: The reactions of fac- [Rh(apt) Design and creation of heterometallic multinuclear complexes have long been one of the most important subjects in synthetic coordination chemistry.1 For this purpose, we have developed a metalloligand approach, in which pre-designed metal complexes with several donor sites are used as a ligand (metalloligand) instead of organic and inorganic ligands, focused on thiolato metal complexes.2 Previously, we showed that fac-[M(aminothiolato-N,S) 3 ]-type complexes act as an Sdonating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Previously, we showed that the octahedral rhodium(III) complex [Rh(aet) 3 ] (aet=2‐aminoethanethiolate) can bind to transition‐metal ions through facially arranged thiolato groups, thereby producing a variety of S‐bridged multinuclear and supramolecular coordination compounds . One example is the reaction of [Rh(aet) 3 ] with Ag + in water, which forms an S‐bridged Ag I 3 Rh III 2 pentanuclear complex, [Ag 3 {Rh(aet) 3 } 2 ] 3+ , which retains the molecular structure of [Rh(aet) 3 ] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we showed that the octahedral rhodium(III) complex [Rh(aet) 3 ] (aet=2‐aminoethanethiolate) can bind to transition‐metal ions through facially arranged thiolato groups, thereby producing a variety of S‐bridged multinuclear and supramolecular coordination compounds . One example is the reaction of [Rh(aet) 3 ] with Ag + in water, which forms an S‐bridged Ag I 3 Rh III 2 pentanuclear complex, [Ag 3 {Rh(aet) 3 } 2 ] 3+ , which retains the molecular structure of [Rh(aet) 3 ] .…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28] One example is the reaction of [Rh(aet) 3 ]w ith Ag + in water, which forms an S-bridged Ag I 3 Rh III 2 pentanuclear complex, [Ag 3 -{Rh(aet) 3 } 2 ] 3+ ,w hich retains the molecular structure of [Rh-(aet) 3 ]. [20][21][22][23][24][25][26][27][28] One example is the reaction of [Rh(aet) 3 ]w ith Ag + in water, which forms an S-bridged Ag I 3 Rh III 2 pentanuclear complex, [Ag 3 -{Rh(aet) 3 } 2 ] 3+ ,w hich retains the molecular structure of [Rh-(aet) 3 ].…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously,w es howed that the octahedral rhodium(III) complex [Rh(aet) 3 ](aet = 2-aminoethanethiolate) can bind to transition-metal ions through facially arranged thiolato groups,thereby producing avariety of S-bridged multinuclear and supramolecular coordination compounds. [20][21][22][23][24][25][26][27][28] One example is the reaction of [Rh(aet) 3 ]w ith Ag + in water, which forms an S-bridged Ag I 3 Rh III 2 pentanuclear complex, [Ag 3 -{Rh(aet) 3 } 2 ] 3+ ,w hich retains the molecular structure of [Rh-(aet) 3 ]. [23] Since [Ag 3 {Rh(aet) 3 } 2 ] 3+ is obtained as ar acemic compound consisting of DD and LL isomers,inwhich the two [Rh(aet) 3 ]u nits have the same chiral configuration (D or L), [23] herein, we treated ay ellow aqueous solution of [Ag 3 {Rh(aet) 3 } 2 ](BF 4 ) 3 with d-penicillamine to isolate optically active species.F rom this reaction, we obtained av ery small amount of 1' as adeep-red crystalline solid.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…In the course of our long-standing program of using thiolato metal complexes as S-donating metalloligands in multinuclear cluster assemblies, , we recently reported the S-bridged trinuclear complex, [Ni­{Rh­(apt) 3 } 2 ] 3+ ([ 1 Rh ] 3+ ; apt = 3-aminopropanethiolate), where fac -[Rh­(apt) 3 ] acts as a tripodal S-donating metalloligand to nickel. In [ 1 Rh ] 3+ , the nickel center adopts a Jahn–Teller distorted octahedral geometry with a +III oxidation state, which is reversibly oxidized and reduced to form nickel centers with +IV and +II oxidation states, respectively. Notably, all of the three species are stable enough to be isolated as single crystals, whose structures were established by X-ray analysis.…”
Section: Introductionmentioning
confidence: 99%